Improving the flotation separation of chalcopyrite from galena through high-temperature air oxidation pretreatment. (January 2022) - Yang, Zhizhao; Geng, Liang; Zhou, Hepeng; Liu, Zishuai; Xie, Fanxin; Yang, Siqi; Luo, Xianping
Highlights: Flotation separation of chalcopyrite and galena can be realized without depressant. The oxidation degree of chalcopyrite surface was much higher than that of galena. The hydrophilic species of FeOOH and CuO were formed on the surface of chalcopyrite. The chemisorption of SBX on the galena surface was still violent after pretreatment. Abstract: A method of air oxidation pretreatment at 170 °C was developed for the selective separation of chalcopyrite and galena. Single mineral and artificially mixed mineral flotation experiments indicated that the hydrophobicity of chalcopyrite was greatly reduced, and galena maintained outstanding floatability after pretreatment by high-temperature air oxidation. Hence, the efficient flotation separation of chalcopyrite and galena was achieved. Zeta potential and FTIR analysis illustrated that the chemisorption strength of collector sodium butyl xanthate (SBX) on the surface of galena was higher than that on chalcopyrite based on the oxidation pretreatment method. XPS analysis proved that oxidation could occur on the surfaces of chalcopyrite and galena with pretreatment by high-temperature air oxidation, but the oxidation extent of chalcopyrite was greater than that of galena. Moreover, the FeOOH and CuO hydrophilic species formed on the chalcopyrite surface greatly increased the hydrophilicity of chalcopyrite and impeded the adsorption of SBX on the chalcopyrite surface. By contrast, the galena surface was extremely difficult to oxidize to PbO during air oxidation at 170 °C due to the high stability, and the chemical reaction of SBX on the galena surface was still violent. Therefore, the flotation separation of chalcopyrite and galena can be efficiently realized using high-temperature air oxidation method to treat minerals.